PENGARUH INFLASI, SUKU BUNGA SBI, NILAI TUKAR RUPIAH TERHADAP USD, PROFITABILITAS, DAN PERTUMBUHAN AKTIVA TERHADAP HARGA SAHAM PERUSAHAAN PEMBIAYAAN DI BURSA EFEK INDONESIA - Iba, Zainuddin; Wardhana, Aditya (JURNAL KEBANGSAAN, 2012)
This research aims at analyzing the influence of inflation rate, sertifikat bank Indonesia (SBI) rate, and currency exchange rate of Rupiah toward US Dollar, companyâs profitability and companyâs asset growth and their impact to financing companyâs stock price partially and simultaneously. The inflation rate, sertifikat bank Indonesia (SBI) rate, and currency exchange rate of Rupiah toward US Dollar, companyâs profitability and companyâs asset growth as independent variables. Financing companyâs stock price as dependent variables. The proposed hypotheses: The inflation rate, sertifikat bank Indonesia (SBI) rate, currency exchange rate of Rupiah toward US Dollar, companyâs profitability and companyâs asset growth have significance influences to the financing companyâs stock price partially and simultaneously. The result of the research has evidenced that inflation rate, sertifikat bank Indonesia (SBI) rate, and currency exchange rate of Rupiah toward US Dollar, corporateâs profitability and asset growth are significantly related to the financing companyâs stock price partially and simultaneously. The research methodology is a survey method by descriptive and verificative research. The data processing uses multiple regression models by SPSS statistical software. Population in this research are registered financing companies listed in Indonesia Stock Exchange (Bursa Efek Indonesia) from 31st March 2004 and still listed until 31st March 2011. The result of coefficient of correlation is 61,2% and itâs a strong relation between independent and dependent variables and 38,8% is the impact of other variables were not researched. Based on simultaneous hypotheses testing using F-test and partial hypotheses testing using t-test, it shows the significant impact between independent and dependent variables. From this result, there is main conclution that the companyâs profitability and SBI rate have strong significant impact from the others to the financing companyâs stock price.